The Scholarly Transformation of Nahdlatul Ulama: Fiqh of Civilization as a Step Towards Embracing the Future - Fathorrahman, Fathorrahman; Masduqi, Anis; Sugitanata, Arif (AL-TAHRIR, 2024)
Nahdlatul Ulama (NU), under the leadership of Yahya Cholil Staquf, has taken significant steps in addressing global challenges and modernity through the concept of "Fiqh of Civilization". This concept aims to broad the understanding of Islamic jurisprudence beyond the Muslim community scale, encompassing inter-civilizational interactions. This research investigates how NU integrates universal Islamic principles with contemporary social, economic, and political dynamics, creating new scholarly constructs relevant to the current era. By utilizing a qualitative-descriptive method based on a literature review, this study analyzes various NU initiatives and programs, such as the Civilization Fiqh Halaqah and the Thought Congress. Findings indicate NU's seriousness in fostering a dynamic and inclusive scholarly discourse, focusing on pluralism, social justice, and environmental sustainability. This study further explores the contributions fiqh of civilization to "Al-Nahdlah Al-Tsaniyah" reflecting a paradigmatic shift in religious understanding and practice. The results show that fiqh of civilization not only reinterprets religious texts but also enrich social interactions and strengthens Islamic identity in a global context. This concept underscores the importance of adapting religious texts to change realities and highlights NU's strategic role in advancing progressive and responsive Islamic thought. The conclusion of this study asserts that fiqh of civilization has facilitated a productive dialogue between Islamic principles and contemporary challenges, essential for the development of a harmonious and sustainable civilization.